2021
DOI: 10.1039/d0ra09723c
|View full text |Cite
|
Sign up to set email alerts
|

Rapid iodine capture from radioactive wastewater by green and low-cost biomass waste derived porous silicon–carbon composite

Abstract: The effective and safe capture and storage of radioactive iodine (129I or 131I) are of significant importance during nuclear waste storage and nuclear energy generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…vely. [6a] As olid-state CP/MAS 13 CNMR spectroscopic study (Figure 1b)revealed broad peaks in the 150-120 ppm (a, b, c) and 110-100 ppm (d) spectral range.T hese features were assigned to the sp 2 -hybridized carbons of the aromatic phenyl and pyrrole rings in the polymer frameworks,r espectively. Peaks between 90 and 100 ppm (e) were also seen that were ascribed to the sp-hybridized acetylene (-CC-) groups, [21] as would be expected for the proposed POPs.F urthermore, sharp signals at about 45 ppm (f) and broad signals at about 30 ppm (g) were seen for all the POPs;t hese were assigned, respectively,tothe methyl and methylene carbon resonances of the calix [4]pyrrole.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…vely. [6a] As olid-state CP/MAS 13 CNMR spectroscopic study (Figure 1b)revealed broad peaks in the 150-120 ppm (a, b, c) and 110-100 ppm (d) spectral range.T hese features were assigned to the sp 2 -hybridized carbons of the aromatic phenyl and pyrrole rings in the polymer frameworks,r espectively. Peaks between 90 and 100 ppm (e) were also seen that were ascribed to the sp-hybridized acetylene (-CC-) groups, [21] as would be expected for the proposed POPs.F urthermore, sharp signals at about 45 ppm (f) and broad signals at about 30 ppm (g) were seen for all the POPs;t hese were assigned, respectively,tothe methyl and methylene carbon resonances of the calix [4]pyrrole.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The distances between the opposing terminal alkynes were 14.1 and 13.6 ,r espectively.T his cavity is large enough to accommodate iodine (ca. 13 CNMR spectroscopy,n itrogen adsorption/desorption isotherm measurements,t hermogravimetric analyses (TGA), powder X-ray diffraction (PXRD) studies,and scanning electron microscopy (SEM).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile,anew signal near 2210 cm À1 corresponding to an asymmetric -CCstretching mode was observed, hinting at the successful formation of networks.A ll five POPs showed absorbances at about 3450 and 2950 cm À1 ,corresponding to the pyrrolic N-Hs tretching and aromatic CÀHs tretching modes,r especti- Angewandte Chemie Forschungsartikel vely. [6a] As olid-state CP/MAS 13 CNMR spectroscopic study (Figure 1b)revealed broad peaks in the 150-120 ppm (a, b, c) and 110-100 ppm (d) spectral range.T hese features were assigned to the sp 2 -hybridized carbons of the aromatic phenyl and pyrrole rings in the polymer frameworks,r espectively. Peaks between 90 and 100 ppm (e) were also seen that were ascribed to the sp-hybridized acetylene (-CC-) groups, [21] as would be expected for the proposed POPs.F urthermore, sharp signals at about 45 ppm (f) and broad signals at about 30 ppm (g) were seen for all the POPs;t hese were assigned, respectively,tothe methyl and methylene carbon resonances of the calix [4]pyrrole.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iodine-containing wastewater produced in the pharmaceutical industries, nuclear power plants and disinfection process of iodophor can result in a series of serious problems, such as contaminating underground water sources and threatening the life of creatures due to its toxicity. [1][2][3][4] Therefore, iodine removal from wastewater is an urgent problem to be solved globally and it is of great importance to improve civil health and boost the sustainable development of the environment. Multiple methods, such as membrane separation, chemical reaction binding and adsorption, have been proposed and applied for the removal of iodine.…”
Section: Introductionmentioning
confidence: 99%